Long-period ocean-bottom motions in the source areas of large subduction earthquakes - Nakamura, Takeshi (Sci Rep, 2015)
Long-period ground motions in plain and basin areas on land can cause large-scale, severe damage to structures and buildings and have been widely investigated for disaster prevention and mitigation. However, such motions in ocean-bottom areas are poorly studied because of their relative insignificance in uninhabited areas and the lack of ocean-bottom strong-motion data. Here, we report on evidence for the development of long-period (10–20 s) motions using deep ocean-bottom data. The waveforms and spectrograms demonstrate prolonged and amplified motions that are inconsistent with attenuation patterns of ground motions on land. Simulated waveforms reproducing observed ocean-bottom data demonstrate substantial contributions of thick low-velocity sediment layers to development of these motions. This development, which could affect magnitude estimates and finite fault slip modelling because of its critical period ranges on their estimations, may be common in the source areas of subduction earthquakes where thick, low-velocity sediment layers are present.